Implementasi Penelitian Hadits: Kritik Sanad dan Matan Hadits - Makhfud Makhfud (Tribakti: Jurnal Pemikiran Keislaman, 2018)
Hadits critic was very easy when Rasulullah was still alive. Because the friends of Rasulullah directly could understand which one was true and not true by confirming to Rasulullah S.A.W. directly. Confirmation system was the first critic toward hadits when Rasulullah was still alive . It did not mean that They suspected him as liar but They carefully kept the truth because Hadits is also the source of Islamic after al-Qur`an. It could make their belief stronger in implementing the Hadits which They directly got from Rasulullah S.W.A. Some priests have decided that confirmation of Hadits in Rasulullah era was important as the birth of hadits critic science.